Методика удосконалення організаційної структури управління будівельного підприємства шляхом формування системи інформаційного забезпечення - Дубінін, Д. В. (Ways to Improve Construction Efficiency, 2014)
Method of optimizing organizational structure of construction enterprises by forming information system. The article deals with the basic concepts as regards the improvement of the organizational structure of a construction company. Classifications of construction companies and organizational structures of a company are submitted. Some measures to improve the organizational structure of a construction company are offered information management system as an example